2011
DOI: 10.1523/jneurosci.0092-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Histone H2A.X as an Early Marker of Neuronal Endangerment following Seizures in the Adult Rat Brain

Abstract: The phosphorylated form of histone H2A.X (γ-H2AX) is a well-documented early, sensitive and selective marker of DNA double-strand breaks (DSBs). Previously we found that excessive glutamatergic activity increased γ-H2AX in neurons in vitro. Here we evaluated γ-H2AX formation in the adult rat brain following neuronal excitation evoked by seizure activity in vivo. We found that brief, repeated electroconvulsive shock (ECS)-induced seizures (three individual seizures within 60 min) did not trigger an increase γ-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 42 publications
(67 reference statements)
1
31
0
Order By: Relevance
“…As further confirmation of the neuroprotective effects of APX2009 after cisplatin treatment, the levels of pH2AX, a marker of DNA damage (Podhorecka et al, 2010;Redon et al, 2010;Crowe et al, 2011), were measured in sensory neuronal cultures in the absence or presence of various E3330 analogs. When cultures were exposed to 10 mM cisplatin for 24 or 48 hours, there is a significant increase in the levels of pH2AX as measured using Western blotting confirming DNA damage by the platinum compound (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As further confirmation of the neuroprotective effects of APX2009 after cisplatin treatment, the levels of pH2AX, a marker of DNA damage (Podhorecka et al, 2010;Redon et al, 2010;Crowe et al, 2011), were measured in sensory neuronal cultures in the absence or presence of various E3330 analogs. When cultures were exposed to 10 mM cisplatin for 24 or 48 hours, there is a significant increase in the levels of pH2AX as measured using Western blotting confirming DNA damage by the platinum compound (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of γH2A.X is associated with cell cycle suspension in proliferating cells [29], as well as NMDA/AMPA receptor stimulation in differentiated neuronal cells [53]. Finally, the presence of γH2A.X predicts neuronal endangerment and death following a pathological state in the adult brain [54]. In the present studies, we detected γH2A.X level to study whether anesthetic isoflurane could induce DNA damage as demonstrated by increase in γH2A.X level.…”
Section: Discussionmentioning
confidence: 99%
“…Third, several lines of evidence support the conclusion that epigenetic factors and mechanisms are functionally deregulated in epilepsy, including analyses performed utilizing human specimens as well as many different animal models (Crowe et al, 2011; Huang et al, 2012; Hwang et al, 2013; Kobow and Blumcke, 2012; Kobow et al, 2009; Kobow et al, 2013; Machnes et al, 2013; Miller-Delaney et al, 2012; Park et al, 2014; Ryley Parrish et al, 2013; Sng et al, 2006; Taniura et al, 2006; Tsankova et al, 2004; Williams-Karnesky et al, 2013; Zhu et al, 2012). One of the most persuasive studies found that, in a rat model of TLE, increased levels of DNA methylation in the hippocampus are associated with epileptogenesis and that adenosine, an endogenous anticonvulsant and anti-epileptogenic factor, exerts these effects via inhibition of DNA methylation (Williams-Karnesky et al, 2013).…”
Section: Epigenetic Mechanisms and Epilepsymentioning
confidence: 92%
“…Parallel studies reveal histone-modifying enzymes (i.e., HDAC2) are deregulated in human TLE neuropathological specimens and in hippocampal tissue from acute and chronic TLE animal models (Huang et al, 2012). Moreover, various alterations in histone PTMs associated with H3, H4, and H2A.X have also been identified in epilepsy models (Crowe et al, 2011; Sng et al, 2006; Taniura et al, 2006; Tsankova et al, 2004). …”
Section: Epigenetic Mechanisms and Epilepsymentioning
confidence: 99%